From Supplier Relations to Triad in the Automotive Industry - Kadzrina Abdul Kadir; Johanim Johari; Darwina Ahmad Arshad (International Journal of Supply Chain Management, 2019)
This paper presents a review of the literature of supplier relations in the automotive industry towards triad and how this has an impact on the supplier selection for buyers. This paper focuses on the automotive sector specifically. The paper suggest that triads reflect the supplier relations attributes in previous literature yet stress on the need for further emphasis on the supplier-supplier relationship